القطاع الخـاص بين حتمية تحقيق النمو الاقتصادي و ضرورة حماية حقوق الإنسان - بن عثمــــان, فوزيــــــة (revue mofakir, 2018)
تأتي هذه الدراسة لتبرز دور القطاع الخاص في مجال حماية حقوق الإنسان، بالنظر إلى دوره المحوري في تحقيق النمو الاقتصادي . من خلال توجيه دور الدولة صوب تدعيم البيئة المواتية لتفعيل النشاط الفردي ضمن إطار القطاع الخاص وتفعيل دور هذا الأخير كشريك حقيقي إلى جانب الدولة في التنمية، وذلك بالاحتكام إلى مبادئ المسؤولية الاجتماعية والاهتمام بقضايا حقوق الإنسان . وسيتم التركيز ضمن هذه الورقة على أهم الحقوق التي يساهم في ضمانها القطاع الخاص خاصة في مجال الحق في العمل والخدمات الاجتماعية والحد من الفقر ورفع مستوى المعيشة .   Abstract: The objective of this study is to show the private sector role as regards the protection of human rights, in view of its main role in achieving the economic development, by being based on social responsibility’s principles and dealing with human right matters. So that we will focus in this study on the main right which the private sector contribute in guaranteeing its existing , especially concerning the right of working, social services, limiting the poverty and raising the standard of living.